2023
DOI: 10.1002/cam4.5605
|View full text |Cite
|
Sign up to set email alerts
|

SLC12A5 promotes hepatocellular carcinoma growth and ferroptosis resistance by inducing ER stress and cystine transport changes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(109 reference statements)
0
11
0
Order By: Relevance
“… 40 Additionally, it has been found that SLC12A5 impedes tumorigenesis in HepG2 cells by impeding cell cycle progression via calcium release into the cytosol during ER stress. 20 While conventionally recognized as a membrane protein crucial for K‐Cl transport, recent evidence unveils that SLC12A5 is also expressed in the nucleus, exerting a tumour‐promoting role. 41 Jiang and colleagues conducted a comprehensive investigation into the role of SLC12A5 across 33 human cancers, demonstrating its potential as a tumour promoter associated with worse overall survival and poor disease‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 40 Additionally, it has been found that SLC12A5 impedes tumorigenesis in HepG2 cells by impeding cell cycle progression via calcium release into the cytosol during ER stress. 20 While conventionally recognized as a membrane protein crucial for K‐Cl transport, recent evidence unveils that SLC12A5 is also expressed in the nucleus, exerting a tumour‐promoting role. 41 Jiang and colleagues conducted a comprehensive investigation into the role of SLC12A5 across 33 human cancers, demonstrating its potential as a tumour promoter associated with worse overall survival and poor disease‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tong and colleagues reported that SLC12A5 promotes tumour progression by regulating ER stress and increases ferroptosis resistance in HCC by controlling intracellular redox balance. 20 In this study, our investigation focused on the gene expressions of biomarkers related to ER stress pathways induced by borax in HepG2 cells. Additionally, we explored the connection between borax‐induced ER stress and apoptotic mechanisms, as well as its impact on SLC12A5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 110 ), curcumin promoted iron apoptosis in colorectal cancer by controlling the expression of vital iron apoptosis indicators Fer 1, SLC7A11, GSH, MDA, and ROS through the PI3K/mTOR pathway. Recent studies have shown that the mTOR-related signaling system can either promote or inhibit ferroptosis in hepatocellular carcinoma cells ( 111 , 112 ). For instance, HU et al.…”
Section: Mechanisms Of Ferroptosis Regulationmentioning
confidence: 99%
“…Ferroptosis is an iron-dependent form of regulated cell death characterized by the accumulation of lipid peroxides. Ferroptosis resistance, the ability of cells or tissues to evade ferroptotic cell death, has been implicated in the development of cell death and various diseases [1][2][3][4], yet its role in lupus still needs to be depicted. Lupus is an autoimmune disease characterized by hypergammaglobulinemia derived from pathogenic B cell behavior [5][6][7].…”
Section: Introductionmentioning
confidence: 99%